A Case Study of Mass Transport during the East-West Oscillation of the Asian Summer Monsoon Anticyclone. (10th October 2017) - Luo, Jiali; Song, Jiayao; Tian, Hongying; Liu, Lei; Liang, Xinlei
Abstract : We use ERA-Interim reanalysis, MLS observations, and a trajectory model to examine the chemical transport and tracers distribution in the Upper Troposphere and Lower Stratosphere (UTLS) associated with an east-west oscillation case of the anticyclone in 2016. The results show that the spatial distribution of water vapor (H2 O) was more consistent with the location of the anticyclone than carbon monoxide (CO) at 100 hPa, and an independent relative high concentration center was only found in H2 O field. At 215 hPa, although the anticyclone center also migrated from the Tibetan Mode (TM) to the Iranian Mode (IM), the relative high concentration centers of both tracers were always colocated with regions where upward motion was strong in the UTLS. When the anticyclone migrated from the TM, air within the anticyclone over Tibetan Plateau may transport both westward and eastward but was always within the UTLS. The relative high concentration of tropospheric tracers within the anticyclone in the IM was from the east and transported by the westward propagation of the anticyclone rather than being lifted from surface directly. Air within the relative high geopotential height centers over Western Pacific was partly from the main anticyclone and partly from lower levels.